The contributions of Abu Hassan Ali bin Hassan Al-Hinai in Arabic language - Elsayed Makki Elbishr Ali Hassan (Tanjong Malim, 2019)
The contributions of Abu Hassan Ali bin Hassan Al-Hinai in Arabic language by Elsayed Makki Elbishr Ali Hassan